Metode Weighted Product Dalam Penerapan Sistem Pendukung Keputusan Pemilihan Fashion Pria - Nicodias Palasara; Feri Prasetyo; Mulyadi Satria; Anastasia Siwi F Utami; Ahmad Sinnun (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management, 2023)
Sales become one of the important aspects in a company. Sales need information to process and run a business. The sales system will still affect the needs and market demands that customers want. This can be seen from the many places that provide internet facilities or facilities to obtain information. And it can not only be enjoyed by the upper class, but all layers can enjoy it at a lower cost. Store that sells various special men's fashion equipment. which includes shirts, bags, backpacks, shoes, jackets, and other men's fashion. It can be known that clothing equipment can affect the business market in the country, both offline and online sales